Perencanaan Saluran Turun Dan Saluran Masuk Serta Pembuatan Grinding Cyl Dengan Material Besi Cor Kelabu Menggunakan Cetakan Permanen - Rohman, Muhamad Endy Nur; , Agus Yulianto, ST, MT (2017)
Grinding cyl function is used as a grinder and additional material from the milled material itself. Cyl grinding manufacture is intended to support light brick-making industry, ceramic industry and other indusrti requiring ..TO components to simplify and shorten the time to production diindustri, then made permanent mold is a mold that can be used repeatedly to increase production grinding sehinnga this cyl. the results obtained cross-sectional comparisons and calculations down channel system 50.4 mm, 14.7 mm and a slag channel inlet 3 mm. Based on the results bercobaan pouring into permanent mold castings, castings showed that the second surface better than the first surface of the castings. Graph CE Meter shows the temperature of 1221.6 ° C during tapping early in the cast in the mold at the start on the chart that reads CE Meter decrease of temperature, the temperature of liquid 1122.1 ° C shape is still liquid to a temperature of solid 1120.0 ° C so that the obtained value of CEL = 4 , 46%; C = 4.00%; and SI = 1.78% where the iron start but still solid red until the temperature of 1060 ° C and hardened within 180 seconds. Results of chemical composition in solid or solid form such as: Fe 93.26%; C 3.06%; 1.80% Si and other elements under 1%. The test results of micro structure in the test section of the specimen visible graphite and cementite hardness and hardness test results of the specimens in the A = 91.27 HRB. B = 90.03 HRB. C = 96.66 HRB and D = 92,28HRB prices and the highest hardness in part C of 96.66 HRB hardness while the lowest prices are in part B of 90.03 HRB. Based on these data we can conclude that each part has varying levels of violence, because each point or section in the test has a carbon content of different. The higher the carbon content the higher the level of violence as well as affecting the physical properties of gray cast iron.Keyword : lidification, molding FCD, spectrometer, microstructure, hardness.